Comparative study of select biochemical markers in cerebrospinal fluid of healthy dogs before and after treatment with nutraceuticals. (28th January 2014) - Galan, A.; Carletti, B.E.; Morgaz, J.; Granados, M.M.; Mesa, I.; Navarrete, R.; Lombardo, R.; Martínez, C.M.; Martín‐Suárez, E.M.
<x xml:space="preserve">Abstract</x> Background Several studies indicate that changes in cerebrospinal fluid (CSF) composition depend on the disease stage and reflect modification of brain energy metabolism (BEM). Also, it has been reported that a decline in cognitive functions may be mitigated by incorporating nutraceuticals in the diet. Objective Assuming the beneficial effect of nutraceuticals on BEM and oxidative damage, the aim of this study was to determine if the administration of a nutraceutical compound results in changes of select CSF biomarkers in healthy adult Beagle dogs. Methods Two separate CSF and blood samples were obtained from 11 healthy adult Beagle dogs, before and after 50 days of treatment with a veterinary combined nutraceutical. CSF analysis included a total nucleated cell count, total protein, glucose, sodium, chloride, potassium, pyruvate, and lactate concentrations, and calculation of lactate/pyruvate ratio. CBC and serum biochemistry were also performed. The Wilcoxon test was used to analyze the significance of the changes after nutraceutical treatment. Results All studied variables remained within reference intervals, before and after treatment. A significant increase in CSF sodium and glucose concentration, and a decrease in lactate levels, was observed after treatment (P < .05), and the lactate/pyruvate ratio was decreased after treatment (P = .05). In serum, sodium and chloride concentrations were significantly increased (P < .05), and creatinine concentration was significantly decreased (P < .05) after treatment. Conclusions After 50 days of treatment with a nutraceutical compound, CSF glucose, sodium, and lactate concentrations, and L/P ratio were significantly different, suggesting an influence of nutraceuticals' administration on CSF composition.